Analisis Location Quotient (LQ) dan Shift Share Kabupaten Sintang Sebelum Dan Sesudah Pemekaran - B01108061, Roni Mashuri (Jurnal Pembangunan dan Pemerataan, 2014)
This descriptive study has three main objectives, the first objective is to determine thegrowth sectors of the economy in Sintang before and after the expansion area, the secondobjective to determine Sintang economic growth compared with the growth of WestKalimantan Province before and after regional expansion, while the goal third to determinethe competitiveness of the economic sectors in Sintang before and after regional expansion.The period before the expansion area is calculated starting in 2000 until in 2003, whileafter the split area is calculated from the year 2004 to the year 2011.These results indicate that the growth of economic sectors Sintang after splitting alarger area than before the expansion area, Sintang economic growth after the split area isalso well above the economic growth of West Kalimantan province, while thecompetitiveness of economic sectors experiencing Sintang rise after the expansion area. Thebest sector Sintang after the expansion area is the construction sector because it has thehighest growth rate and competitiveness both in the province of West Kalimantan.Key words : Regional Expansion Sintang